Deconstruction of Landreform Policy in Indonesia (Study of Regulation of President Number 86 Of 2018 about Agrarian Reforms) - Muhammad Fikri Alan (UIN Sunan Kalijaga Yogyakarta, 2021)
There is a large gap between the regulation of Land Reform in the UUPA, with Presidential Regulation No. 86 of 2014 concerning Agrarian Reform. On one hand, the UUPA states that Land Reform is a systematic effort by the state to rearrange ownership, control, and access to land. Whereas on the other hand, the Presidential Regulation stipulates that Land Reform is equated with Agrarian Reform, and the scope of the arrangement covers the arrangement of access and arrangement of assets. Nevertheless, this Perpres then only means Landreform merely as the legalization of assets, which is part of the structuring of assets. One thing that is very different from the UUPA version of Landreform. This study aims to uncover the causes of the gap, and formulate an ideal form of regulation. This study uses the normative juridical method, with the statutory approach and the conceptual approach. The results of this study are first, the difference in regulation is caused by the two legal products born from different features or characteristics. The Perpres on Agrarian Reform was born in a regime that tends to be instrumentalist liberalism, while the UUPA was born from a legal regime that tends to be socialistic-communal. Second, there are at least 2 things that need to be fixed in the Landreform settings. First, the affirmation of the state's position in implementing Landreform, whether to continue to use the instrumentalist, socialistic-communal liberalistic model, or the conception of a welfare state that is native to Indonesia. Second, TORA must be the object of Land Procurement for Public Interest. Thus, Landreform activities can become the main national agenda and must be carried out.